Thorax, Trachea, and Lung Ultrasonography in Emergency and Critical Care Medicine: Assessment of an Objective Structured Training Concept. (27th November 2013) - Breitkreutz, Raoul; Dutiné, Martina; Scheiermann, Patrick; Hempel, Dorothea; Kujumdshiev, Sandy; Ackermann, Hanns; Seeger, Florian Hartmut; Seibel, Armin; Walcher, Felix; Hirche, Tim Oliver
Abstract : Background and Study objective . Focused lung ultrasound (LUS) examinations are important tools in critical care medicine. There is evidence that LUS can be used for the detection of acute thoracic lesions. However, no validated training method is available. The goal of this study was to develop and assess an objective structured clinical examination (OSCE) curriculum for focused thorax, trachea, and lung ultrasound in emergency and critical care medicine (THOLUUSE). Methods . 39 trainees underwent a one-day training course in a prospective educational study, including lectures in sonoanatomy and -pathology of the thorax, case presentations, and hands-on training. Trainees' pre- and posttest performances were assessed by multiple choice questionnaires, visual perception tests by interpretation video clips, practical performance of LUS, and identification of specific ultrasound findings. Results . Trainees postcourse scores of correct MCQ answers increased from 56 ± 4 % to 82 ± 2 % (mean± SD; P < 0.001 ); visual perception skills increased from 54 ± 5 % to 78 ± 3 % (P < 0.001 ); practical ultrasound skills improved, and correct LUS was performed in 94%. Subgroup analysis revealed that learning success was independent from the trainees' previous ultrasound experience. Conclusions . THOLUUSE significantly improves theoretical and practical skills for the diagnosis of acute thoracic lesions. We propose to implement THOLUUSE in emergency medicine training.